An update on polygalacturonase-inhibiting protein (PGIP), a leucine-rich repeat protein that protects crop plants against pathogens - Kalunke, Raviraj M.; Tundo, Silvio; Benedetti, Manuel; Cervone, Felice; De Lorenzo, Giulia; D'Ovidio, Renato (Frontiers in Plant Science, 2015)
Polygalacturonase inhibiting proteins (PGIPs) are cell wall proteins that inhibit the pectin-depolymerizing activity of polygalacturonases secreted by microbial pathogens and insects. These ubiquitous inhibitors have a leucine-rich repeat structure that is strongly conserved in monocot and dicot plants. Previous reviews have summarized the importance of PGIP in plant defence and the structural basis of PG-PGIP interaction; here we update the current knowledge about PGIPs with the recent findings on the composition and evolution of pgip gene families, with a special emphasis on legume and cereal crops. We also update the information about the inhibition properties of single pgip gene products against microbial PGs and the results, including field tests, showing the capacity of PGIP to protect crop plants against fungal, oomycetes and bacterial pathogens.